The Short Form of the Breastfeeding Self-Efficacy Scale as a Prognostic Factor of Exclusive Breastfeeding among Mandarin-Speaking Chinese Mothers. (November 2016) - Ip, Wan-Yim; Gao, Ling-Ling; Choi, Kai-Chow; Chau, Janita Pak-Chun; Xiao, Yang
Background: Little is known about the effect of maternal perceived breastfeeding self-efficacy on the exclusive breastfeeding rate at 6 months postpartum in mainland China. Objective: The aim of this study was to examine the relative effect of maternal breastfeeding self-efficacy and selected relevant factors on the exclusive breastfeeding rate at 6 months postpartum. The internal consistency and construct validity of the Chinese (Mandarin) version of the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF) were also examined. Methods: This was a prospective cohort study conducted at a regional teaching hospital in Guangzhou, China. A total of 562 in-hospital mothers who were within 72 hours postpartum were recruited to the study and followed up by telephone for 6 months. Results: Although all of the mothers breastfed their babies within 72 hours postpartum, only 25% of the mothers breastfed exclusively. The mean survival time of continuation of exclusive breastfeeding was 16.7 days. The proportion of mothers who breastfed exclusively after discharge was 14.8%, 2.0%, and 0.2% at 1, 4, and 6 months, respectively. Cox regression analysis revealed that the mothers who had a higher BSES-SF score at baseline, underwent cesarean section, and practiced exclusive breastfeeding within 72 hours after delivery were significantly associated with a lower hazard of discontinuation of exclusive breastfeeding before 6 months postpartum. Conclusion: The exclusive breastfeeding rate among Chinese women is far from satisfactory. The Chinese (Mandarin) version of the BSES-SF can help in identifying mothers who need more support for exclusive breastfeeding before 6 months postpartum.